Knowledge of the female athlete triad and relative energy deficiency in sport among female cross-country athletes and support staff - Lodge, M. T.; Ackerman, K. E.; Garay, J. (Journal of Athletic Training, 2022)
Context: Female endurance athletes exhibit an increased risk of the female athlete triad (Triad) and relative energy deficiency in sport (RED-S). The triad and RED-S are conditions that involve the health and performance consequences of low energy availability. Few authors of studies to date have assessed the knowledge that athletes, coaches, and athletic trainers (ATs) have regarding the Triad or RED-S. Proper education has been shown to be effective in increasing knowledge of sports medicine concerns for athletes, yet no known continuing education programs for the Triad or RED-S exist at collegiate institutions.